The relationship between earnings management and audit opinion - Dang, Ngoc Hung; Tran, Manh Dung (Business: Theory and Practice, 2025)
This study is conducted to investigate the relationship between earnings management (EM), audit quality (AQ) and qualified opinion of financial statements (AO) of listed firms on Vietnam Stock Exchange. Data were collected from 499 listed firms from 2018 to 2020 with 1,497 observations, of which 101 are observed with qualified opinions. Regressions of Logit and GLS are employed. The results reveal that earnings management has a positive relationship with qualified opinion, while audit quality has a negative association with qualified opinion and earnings management. In this research, we consider the interaction of audit quality with earnings management and qualified opinion. An interesting finding is that the impact of audit quality is weaker than that of earnings management and qualified opinion, so the interaction variable has a positive relationship with both qualified opinion and earnings management. Based on the findings, several suggestions are proposed for users of financial statements and auditors as well to assess the appropriateness of the opinion that is not an unqualified opinion.